Performance of a novel recycling magnetic flocculation membrane filtration process for tetracycline-polluted surface water treatment - Wang, Yufei (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
A recycling magnetic flocculation membrane filtration (RMFMF) process integrating circulating coagulation, magnetic enhanced flocculation and membrane filtration was investigated for the treatment of surface water micro-polluted by tetracycline, a typical pharmaceutical and personal care product. A bench-scale experiment was conducted and several water quality parameters including turbidity, ultraviolet absorbance at 254 nm (UV254), total organic carbon and tetracycline concentration were evaluated, taking coagulation membrane filtration and magnetic flocculation membrane filtration processes as reference treatments. The experimental results showed that at the optimum doses of 20 mg·L-1 ferric chloride (FeCl3), 4 mg·L-1 magnetite (Fe3O4) and 6 mg·L-1 reclaimed magnetic flocs in RMFMF processes, removal efficiencies of above evaluated parameters ranged from 55.8% to 92.9%, which performed best. Simultaneously, the largest average particle size of 484.71 μm and the highest fractal dimension of 1.37 of flocs were achieved, which did not only present the best coagulation effect helpful in enhancing the performance of removing multiple contaminants, but also lead to the generation of loose and porous cake layers favouring reduced permeate flux decline and membrane fouling